Neville Probert interviewed by Rob Linn for the E.A. Crome aviation oral history project - Probert, Neville, 1951-; Linn, Rob. (2004)
Neville Probert, engineer and CASA manager, talks about his education and completing his studies at the University of WA in engineering; his cadetship with Commonwealth Government; being appointed to a position in Dept of Supply in Melbourne; his passion for aviation; his interest in gliding; becoming a Victorian Motorless Flight Group instructor; joining the Airworthiness Branch of Dept. of Transport in 1978; his assessment of new types of aircraft into Australia, e.g. Airbus A300 and Boeing 767 as wide-bodied aircraft and the debate about these aircraft; the roles of TAA and Ansett; Bob Taylor, Head of Airworthiness training school in Melbourne; his move to Canberra (1983); his daily involvement with aviation from aircraft to balloons and airships as well as Australian made aircraft; the role of Airworthiness branch in early 1980s; the increasing involvement of Minister and Parliament and other government agencies; role of Rob Elder in liaison with Minister; the various changes in departments before being separated to become the Civil Aviation Authority (CAA).
Probert discusses the 1988 Air Navigation Act; the Civil Aviation Act; the Henry Bosche report recommendations; air accidents in 1993 and 1994; the importance of the Monarch and Seaview inquiries; the growth of civil and general aviation in Australia; the 'Plane Safe' report and its effect on CAA; the creation of Civil Aviation Safety Authority (CASA) and Air Services Australia (ASA) (1995), as statutory authorities; how CASA (July 1995) was primarily a safety regulator; the role of Airworthiness Standards and the alteration when CASA was established; a new set of regulations for certification of aircraft (1998); how the internet has transformed access to information and business practices; the rewriting of civil aviation regulations since 1997; the termination of CASA Board and appointment of Bruce Byron as CEO; his life's interest in aviation and gratitude to those who encouraged him.
Recorded on 18 March 2004 at Canberra, A.C.T.
Also available online
Timed summary and corrected transcript (typescript, 44 leaves).
Keywords: Probert, Neville, -- 1951- -- Interviews; Australia. -- Civil Aviation Safety Authority; Engineers -- Australian Capital Territory -- Interviews; Aeronautics -- Law and legislation -- Australia; Aeronautics -- Safety measures; Engineers